Short-term Outcome of Coronary Artery bypass Graft Surgery in Diabetics at Ibrahim Cardiac Hospital & Research Institute (Ibrahim Cardiac Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/icmj.v2i1.17381 Ibrahim Cardiac Med J 2012; 2(1): 8-11